Content curation and journalism: exploratory scoping review and expert opinion - Carlos Lopezosa; Javier Guallar; Lluís Codina; Mario Pérez-Montoro (Revista Mediterránea de Comunicación)
This work uses the scoping review format to embrace a systematic review of content curation and journalism. This initially entailed an analysis of scientific studies on the process of content curation in the media with a view to establishing their academic impact, identifying their characteristics, and determining their academic evolution. Having established the subjects and the types of studies performed, the resulting document bank was then analysed. Next, semi-structured interviews were held with the researchers who emerged from the scoping review. The results show 2020 to be the year in which the greatest number of academic works were published in this area. Research content notably included studies on content curation and new journalistic formats, curation on social media and online tools, algorithmic curation and content curation and misinformation. Lastly, the data from the 13 interviews helped both to expand knowledge of what content curation in journalism is and to understand its application in current and future journalism work, as well as yielding some benchmark examples of content curation in journalism.